IMPLEMENTATION OF BEHAVIORAL AND COGNITIVE THEORIES IN THE ARABIC LANGUAGE LEARNING CURRICULUM: A CONCEPTUAL REVIEW - Maghfurin, ِAhmad; Maisaroh, Irfatin; Himawan Akbar, M. Aziz; Ramadhan, M. Rizki; Bahaudin, Moh. Ikhsan (STIQ Amuntai, 2023)
This conceptual overview comprehensively explores the seamless blending of behavioristic and cognitivistic theories within the Arabic language curriculum. It thoroughly explores behaviourism's and cognitivism's theoretical underpinnings, explaining how each has contributed differently to the complex language learning process. The focus behaviourism places on visible behaviour and outside cues are essential to creating vocabulary drills, structured activities, and reinforcement strategies. Conversely, cognitivism emphasizes the learner's mental processes and encourages active participation through assignments requiring problem-solving, comprehension exercises, and critical thinking. By exploring efficacious pedagogical approaches derived from these fundamental beliefs, instructors can enhance students' competency in Arabic. The essay emphasizes how teachers can skillfully combine behavioristic and cognitivistic ideas, drawing on their advantages to create a well-rounded and comprehensive language learning program. This methodology upholds inclusivity and attends to a range of learning styles and personal preferences, thereby enhancing language learning and cultivating a more profound understanding of Arab culture among students inside and outside the Arab world.Keywords: Arabic learning, behaviorism, cognitivism, language curriculum, integration